ESR spectroscopy identifies inhibitory Cu2+ sites in a DNA-modifying enzyme to reveal determinants of catalytic specificity - Yang, Zhongyu; Kurpiewski, Michael R; Ji, Ming; Townsend, Jacque E; Mehta, Preeti; Jen-Jacobson, Linda; Saxena, Sunil (Proceedings of the National Academy of Sciences - PNAS, 2012)
The relationship between DNA sequence recognition and catalytic specificity in a DNA-modifying enzyme was explored using paramagnetic Cu2+ ions as probes for ESR spectroscopic and biochemical studies. Electron spin echo envelope modulation spectroscopy establishes that Cu2+ coordinates to histidine residues in the EcoRI endonuclease homodimer bound to its specific DNA recognition site. The coordinated His residues were identified by a unique use of Cu2+-ion based long-range distance constraints. Double electron-electron resonance data yield Cu2+-Cu2+ and Cu2+-nitroxide distances that are uniquely consistent with one Cu2+ bound to His114 in each subunit. Isothermal titration calorimetry confirms that two Cu2+ ions bind per complex. Unexpectedly, Mg2+-catalyzed DNA cleavage by EcoRI is profoundly inhibited by Cu2+ binding at these hitherto unknown sites, 13 Å away from the Mg2+ positions in the catalytic centers. Molecular dynamics simulations suggest a model for inhibition of catalysis, whereby the Cu2+ ions alter critical protein-DNA interactions and water molecule positions in the catalytic sites. In the absence of Cu2+, the Mg2+-dependence of EcoRI catalysis shows positive cooperativity, which would enhance EcoRI inactivation of foreign DNA by irreparable double-strand cuts, in preference to readily repaired single-strand nicks. Nonlinear Poisson-Boltzmann calculations suggest that this cooperativity arises because the binding of Mg2+ in one catalytic site makes the surface electrostatic potential in the distal catalytic site more negative, thus enhancing binding of the second Mg2+. Taken together, our results shed light on the structural and electrostatic factors that affect site-specific catalysis by this class of endonucleases.